Pengaruh Disiplin Kerja Dan Beban Kerja Terhadap Kinerja Karyawan Pada Pt Surya Ratu Decor Kota Tangerang Selatan - Fina Durotul Bahiyah; Uswatun Chasanah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstract - This study aims to determine the effect of work discipline and workload on employee performance at PT Surya Ratu Decor, South Tangerang City. The type of research used is quantitative research. The population in this study were all 65 employees of PT Surya Ratu Decor, with a saturated sampling technique so that the entire population was used as a research sample. The results of multiple regression analysis showed a coefficient of determination (R²) of 0.913, which means that 91.3% of employee performance variations can be explained by work discipline and workload variables together, while the remaining 8.7% is influenced by other factors outside the study. The results of the t test showed that work discipline had a significant effect on performance with a calculated t value = 17.981> t table = 1.669 and sig. 0.000 <0.05, and workload had a significant effect with a calculated t value = 25.159> t table = 1.669 and sig. 0.000 <0.05. The simultaneous F test obtained a calculated F value = 335.275 > F table = 3.145 with sig. 0.000 < 0.05, which means that work discipline and workload together have a positive and significant effect on the performance of PT Surya Ratu Decor employees in South Tangerang City.